San Martin Regional Health System policy in reduction of child malnutrition: application in Peru of the Health Systems Assessment approach - Mendoza-Arana, Pedro (2015)
Introduction: Chronic infant malnutrition is one of the main public health issues in Peru and in the world. Objectives: To determine achievements and limitations of a regional policy against chronic infant malnutrition in a Region of Peru. Design: Qualitative study, using the Health System Assessment Approach, as promoted by the World Health Organization. Setting: San Martin Region, Peru. Participants: Managers and professionals working at the Health Region as well as users and non users of the services. Interventions: In June and July 2014 semistructured interviews were conducted with health managers and workers at regional and local levels as well as with services users and non users. Main outcome measures: Bottlenecks in the reduction of child malnutrition. Results: Bottlenecks for each of the model components -governance, financing, provision, health resources, drugs, and information system- were identified. Conclusions: Learned lessons from the results and validated in workshops with the participants are drawn.